2012
DOI: 10.1149/2.005202ssl
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Al and Ni Top Electrodes in Resistive Switching Behaviors of Yb2O3-Based Memory Cells

Abstract: In this letter, the effect of Al and Ni top electrodes in resistive switching behavior of Al/Yb 2 O 3 /TaN and Ni/Yb 2 O 3 /TaN memory devices is proposed. The Al/Yb 2 O 3 /TaN memory device demonstrates no such switching performance as applying bias on both top and bottom electrodes, whereas the Ni/Yb 2 O 3 /TaN reveals the bipolar memory switching behavior with a high resistance ratio of 10 4 for over 200 cycles of switching responses and good data retention with memory window of about 10 5 at 85 • C, as ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…Therefore, it can be reasonably concluded that there are sufficient number of defects existing in the device reflecting the concentration of oxygen vacancies. Figure 2(b) shows the XPS trace spectrum in which O 1 s energy state at about 530 eV corresponds to TaON due to nonlattice oxygens29. While, Ta 4p 3/2 peak shows slightly asymmetric shape and binding energy of this peak has been shifted to higher energy as compared to its value for metallic Ta 4p 3/2 (~404 eV) supporting the formation of TaON because of the larger electronegativity of oxygen30.…”
Section: Resultsmentioning
confidence: 93%
“…Therefore, it can be reasonably concluded that there are sufficient number of defects existing in the device reflecting the concentration of oxygen vacancies. Figure 2(b) shows the XPS trace spectrum in which O 1 s energy state at about 530 eV corresponds to TaON due to nonlattice oxygens29. While, Ta 4p 3/2 peak shows slightly asymmetric shape and binding energy of this peak has been shifted to higher energy as compared to its value for metallic Ta 4p 3/2 (~404 eV) supporting the formation of TaON because of the larger electronegativity of oxygen30.…”
Section: Resultsmentioning
confidence: 93%
“…On applying positive bias, at the anode, an electrochemical reaction occurs that separates the oxygen ions from the regular oxygen sites and these oxygen anions can move under the effect of applied electric field which is equivalent to the drift of oxygen vacancies 57 . This electrochemical reaction can be written in Krὅger-vink notations 58 as; where O O represents an oxygen ion on a regular site, O −2 is oxygen anions and V O ++ denotes oxygen vacancies with a double positive charge. If the anode is gold, platinum or another noble metal, it can receive the electrons from the oxygen anions and it may lead to the evolution of oxygen gas and leaves the oxygen vacancies behind 59 ;
Figure 6 Schematic representation of ( a ) Pristine state with top (Al) and bottom (FTO) electrodes, ( b ) Electroforming process, ( c ) Low resistance state with a conducting channel in CFO layer and oxygen diffusion layer near Al electrode, ( d ) Reset process, when oxygen ions are coming back from oxygen diffusion layer to CFO layer, ( e ) and ( f ) High resistance state and Set process.
…”
Section: Resultsmentioning
confidence: 99%
“…An electrochemical reaction occurs when a forward bias is applied to the top Au electrode of the device. This electrochemical reaction can be written in Krὅger-vink notations as [55]: O represents oxygen ions. The electrochemical reaction separates oxygen ions from the regular oxygen sites, and these oxygen ions can drift under the applied electric field, which is equivalent to the movement of the oxygen vacancy [56].…”
Section: Mechanism Discussionmentioning
confidence: 99%